A Study on Awareness of Tuberculosis among the Population of the Field Practice Area of Urban Health Centre, Panagal, Nalgonda District, Andhra Pradesh. - Dr.Karri Vijaya, Dr.Epari Ravi Kiran, (International Journal of Scientific Research and Management (IJSRM), 2017)
A descriptive cross sectional study using Simple Random Sampling technique was used to select a sample of310 houses from universe of 2373 houses of during the time period of 28th of May to 28th of July for a period oftwo months. There were 171 ((55.2%) males and 139 (44.8%) females in the study population. Most of thestudy population were of the age group of 20-29 years. The average age of male was 41.67 years and that offemales was 38.10 years. About 51.9% of the study population had not heard about Tuberculosis, Cough withsputum was the predominant symptom known by most of the study population. Literacy status also played arole as in the study seen that more literate a person more was awareness. Only 13.6% of the total respondentswere able to say that the gold standard i.e. the sputum examination is required in case of Tuberculosis.Majority (68.7%) were optimistic that tuberculosis is curable. Majority (57.1%) preferred Governmenthospitals to Private Hospitals for diagnosis and treatment and therapy of choice was Allopathy ( 85.8%).77.1% of the study population were aware of the presence of DOTS center in UHC, Panagal. Only 67.7%were aware that Anti TB drugs were given on ‘gratis’ in Government Hospitals. Majority (20.0%) of the studypopulation heard about TB from mass media. Majority (79.9%) were aware of BCG Vaccination and majorityof them who were aware said that it should be given as a part of routine immunization to an infant. Thelacunae in the awareness about the epidemiology, diagnosis treatment, precautions, preventive measures takenfor tuberculosis, DOTS regimen, DOTS Center and BCG vaccination, as observed in the study can bemitigated by a multipronged approach utilizing the public-private partnership.